STORYTELLING USING WAYANG KANCIL TO ENHANCE THE UNDERSTANDING OF PROSOCIAL BEHAVIOR FOR PRESCHOOL CHILDREN - Tri Winarsih; Wisjnu Martani (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2018)
The prosocial behavior of preschool children hasn’t developed, so it is much needed to conduct some ways to develop the prosocial behavior. Storytelling using Wayang Kancil is one of the wealth of Indonesia Nation. It is expected to be an interesting media that can stimulate prosocial behavior of preschool children. The purpose of this study is to find whether story telling using Wayang Kancil can enhance the understanding of prosocial behavior for preschool children. This study uses quasi-experimental method, which involves two subject groups from two Kindergartens as experimental and control group. The implementation of storytelling using Wayang Kancil is delivered by storyteller. The knowledge measurement of prosocial behavior for subject is well conducted before and after the treatment. The measurement is conducted by giving stimulus like pictorial story to the subjects. After that, the subject’s answer is given score depends on scoring criteria. The analysis data uses Mann-Whitney U Test that shows the significant difference in understanding prosocialattitude between experimental and control groups (Z=-3,137; p=0,002 (p<0,01)). The understanding of prosocial behavior in experimental group is higher than the control group.